2008
DOI: 10.1021/pr7007797
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Head-and-Neck Cancer Biomarkers Previously Discovered and Identified Using iTRAQ-Labeling and Multidimensional Liquid Chromatography−Tandem Mass Spectrometry

Abstract: Diagnostic oncoproteomics is an emerging field; at present, studies on evaluation of prognostic utility of potential biomarkers identified using proteomic techniques are limited. Analysis with isobaric mass tags (iTRAQ) by multidimensional liquid chromatography-mass spectrometry (LC-MS/MS) to identify proteins that are differentially expressed in human head-and-neck/oral squamous cell carcinomas (HNOSCCs) versus noncancerous head-and-neck tissues has led to the discovery, identification, and verification of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
88
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 62 publications
8
88
0
2
Order By: Relevance
“…To minimize technical variations and improve the reliability of protein quantification, a variety of sophisticated stable isotope labeling techniques have been developed for MS-based proteomics analysis, including chemical (32,33), metabolic (34,35), and enzymatic (36 -38) labeling techniques. Improvements in the quality and accuracy of quantitative proteomics analysis via such stable isotope labeling strategies have facilitated the discovery of potential tumor markers in malignancies such as OSCC/HNSCC (16,39,40).…”
mentioning
confidence: 99%
“…To minimize technical variations and improve the reliability of protein quantification, a variety of sophisticated stable isotope labeling techniques have been developed for MS-based proteomics analysis, including chemical (32,33), metabolic (34,35), and enzymatic (36 -38) labeling techniques. Improvements in the quality and accuracy of quantitative proteomics analysis via such stable isotope labeling strategies have facilitated the discovery of potential tumor markers in malignancies such as OSCC/HNSCC (16,39,40).…”
mentioning
confidence: 99%
“…Recently, Matta et al verified the consistently increased expression of 14-3-3 zeta and sigma proteins in human head-and-neck/oral squamous cell carcinomas versus noncancerous headand-neck tissues (36). The authors also suggested the involvement of these proteins in the development of headand-neck cancer and their association with adverse disease outcome.…”
Section: Discussionmentioning
confidence: 94%
“…The systematic and rigorous assessment of positive PVs and negative PVs for prognostic biomarker was carried out as described earlier by us. 38 Heagerty and Zheng method of time-dependent receiver operator curve and area under the curve was used for the survival model. 40 The R-package risk set ROC was used to apply the standard Cox regression output and obtain estimates of time-dependent sensitivity and specificity, and time-dependent receiver operator curves.…”
Section: Discussionmentioning
confidence: 99%
“…As per the hospital protocol, oral squamous cell carcinoma patients with T 1 and T 2 tumors were treated with radical surgery alone, whereas the majority of patients with T 3 and T 4 disease were treated with radical surgery followed by postoperative radical radiotherapy as described by us. 38 The patients were revisited clinically on a regular basis and the time to recurrence was recorded. If a patient died, the survival time was censored at the time of death; the medical history, clinical examination, and radiological evaluation were used to determine whether the death had resulted from recurrent cancer (relapsing patients) or from any other causes.…”
Section: Follow-up Studymentioning
confidence: 99%
See 1 more Smart Citation